2016
DOI: 10.1111/trf.13550
|View full text |Cite
|
Sign up to set email alerts
|

Severe bleeding complications other than intracranial hemorrhage in neonatal alloimmune thrombocytopenia: a case series and review of the literature

Abstract: Bleeding complications other than ICH may be more extensive, and the presentation of FNAIT may have a greater spectrum than previously described. A high index of suspicion on the possible diagnosis of FNAIT with any bleeding complication in a fetus or neonate may enable adequate diagnostics, adequate treatment, and appropriate follow-up in future pregnancies, as is especially relevant for FNAIT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 21 publications
0
30
0
1
Order By: Relevance
“…[3][4][5][6] In the absence of population-based screening programs, the diagnosis of FNAIT is usually made after an incidental finding of neonatal thrombocytopenia or because of bleeding complications ranging from bruising or petechiae to intracranial hemorrhage in the fetus or newborn.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6] In the absence of population-based screening programs, the diagnosis of FNAIT is usually made after an incidental finding of neonatal thrombocytopenia or because of bleeding complications ranging from bruising or petechiae to intracranial hemorrhage in the fetus or newborn.…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with other studies is relatively difficult due to the fact that the majority of authors have calculated FBS-related fetal loss and adverse outcome rates in relation to the total number of treated fetuses, rather than the total number of procedures performed in this population, which, by definition, would result in an higher reported rate of such complications [9, 12, 16, 18-21] (Appendix 1). Two reports did calculate the risk compared to the total number of procedures: Berkowitz et al [21] reported a rate of pregnancy loss similar to our data (0.6 vs. 0.8%) with, however, a rate of other adverse outcomes five times higher than in our series (6 vs. 0.8%), and Overton et al [19] reported a fetal loss rate of 2.4% (2/84 procedures) in a small series of 12 cases, including an unexplained fetal death occurring 7 days after an uncomplicated PLT IUT.…”
Section: Discussionmentioning
confidence: 99%
“…Our single FBS-related fetal loss (0.8%) occurred due to severe abdominal hemorrhage during FBS in a severely thrombocytopenic fetus (PLT count of 1 × 10 9 /L) in an (IVIG) untreated pregnancy. This was also prior to the recognition of the crucial importance of always having PLTs ready for transfusion at any FBS of a potentially thrombocytopenic fetus, which became routine practice following the report of Paidas et al [14-16]. There were no fetal losses in any of the IVIG-treated cases.…”
Section: Discussionmentioning
confidence: 99%
“…It is a rare, but potentially life threatening disorder with intracranial hemorrhage (ICH) as the most severe complication. Severe gastrointestinal and pulmonary hemorrhages have also been reported [1]. Antibodies against human platelet antigen (HPA)-1a are accountable for nearly 85% of FNAIT cases [2].…”
Section: Introductionmentioning
confidence: 99%